Cities and their spaces. Concepts and their use in Europe. - (:unkn) unknown (Böhlau, 2014)
In der Stadtgeschichtsforschung spielen der Raum, die Nutzung von Raum und die Erinnerungskulturen im Kontext des Raumes seit einigen Jahren eine große Rolle. Die überwiegend englischsprachigen Beiträge des Bandes thematisieren diesen "spatial turn", wobei vor allem die Funktionen der Stadt - etwa Markt, Handel und Stadtentwicklung -, der Stadtraum und seine Repräsentation, die Stadt und ihr "Hinterland" sowie die Entwicklung von Stadtvierteln am Beispiel europäischer Städte in Mittelalter und Neuzeit vorgestellt werden.

For several years, space has been developing into an issue of growing importance in the field of urban history. The uses of space as well as memorial cultures in a spatial context have attracted a particular interest. The contributions to the present volume, predominantly written in English, engage with this "spatial turn". They focus especially on the functions of the city (e.g. market, commerce) and city development, on the city space and its representation, on the city and its "hinterland", and on the development of urban districts. These topics will be discussed with reference to European cities in the medieval and the modern periods.
Keywords: Stadtgeschichte; Raumnutzung; Stadtraum; Öffentlicher Raum; Topographie; Stadtviertel; Stadtumland; Stadtgeschichtsforschung; Mittelalter; Neuzeit; Raumvorstellung; Hinterland